Do gramado às páginas : a crônica de futebol na imprensa no Brasil - Figueira, Diego Marques (2018)
Not by far the exclusive interest of sports journalists, football has always been part of the imagination of national writers. Chronicles about this sport are a fundamental part of both its history and that of national journalism and literature. At the same time literary genre and journalism, the chronicle, ephemeral on newspaper pages, only seems perishable when dealing with a matter as mundane as football. Perhaps its ephemerality is what makes it great. For more than a century the football chronicle informs and amuses, analyzes and entertains and thus approaches itself from people and captivates the reader – possibly more than necessary news about finance or an educational novel. This dissertation presents and analyzes the trajectory of the football chronicle in newspapers and magazines (also in electronic media) in Brazil ever since those texts were journalistic and opinionated until they came to be considered literature. The main theoretical source of this dissertation is the theory of the chronicle and its exercise as everyday literature, here applied to football, creating a Brazilian subgenre, essentially. It is the perenniality of this type of text and the evolution of its style this work will analyze. By showing different chronicles from different times, it is intended to show how this kind of chronicle was affected by the passage of time and the development of the media in which it was developed.